Reference values of left heart echocardiographic dimensions and mass in male peri-pubertal athletes. (29th August 2020) - Cavarretta, Elena; Maffessanti, Francesco; Sperandii, Fabio; Guerra, Emanuele; Quaranta, Federico; Nigro, Antonia; Minati, Monia; Rebecchi, Marco; Fossati, Chiara; Calò, Leonardo; Pigozzi, Fabio
Abstract: Background: Several articles have proposed reference values in healthy paediatric subjects, but none of them has evaluated a large population of healthy trained adolescents. Design: The study purpose was to establish normal echocardiographic measurements of left heart (aortic root, left atrium and left ventricular dimensions and mass) in relation to age, weight, height, body mass index, body surface area and training hours in this specific population. Methods: We retrospectively evaluated 2151 consecutive, healthy, peri-pubertal athletes (100% male, mean age 12.4 ± 1.4 years, range 8–18) referred to a single centre for pre-participation screening. All participants were young soccer athletes who trained for a mean of 7.2 ± 1.1 h per week. Results: Left ventricular internal diameters, wall thickness, left ventricular mass, aortic root and left atrium diameters were significantly correlated to age, body surface area, height and weight ( p < 0.01). Age, height, weight and body surface area were found associated with chamber size, while body mass index and training hours were not. Inclusion of both age and body size parameters in the statistical models resulted in improved overall explained variance for diameters and left ventricular mass. Conclusion: Equations, mean values and percentile charts for the different age groups may be useful as reference data in efficiently assessing left ventricular parameters in young athletes.